2020
DOI: 10.1111/cen.14340
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction and quality of life in hypothyroidism: An online survey by the british thyroid foundation

Abstract: Objective Dissatisfaction with treatment and impaired quality of life (QOL) are reported among people with treated hypothyroidism. We aimed to gain insight into this. Design and patients We conducted an online survey of individuals with self‐reported hypothyroidism. Results Nine hundred sixty‐nine responses were analysed. Dissatisfaction with treatment was common (77.6%), and overall QOL scores were low. Patient satisfaction did not correlate with type of thyroid hormone treatment, but treatment with combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 48 publications
(64 reference statements)
0
77
0
1
Order By: Relevance
“…In the same way, Mitchell et al observed that patients treated with DET or an LT3/LT4 combination showed better QOL than patients with LT4 monotherapy. Nevertheless, these differences disappeared when introducing other elements in the analysis (prior healthcare experiences and expectations on treatment) [57]. This study suggested that improving the patient experience and clarifying expectations at diagnosis could improve satisfaction and quality of life [57].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In the same way, Mitchell et al observed that patients treated with DET or an LT3/LT4 combination showed better QOL than patients with LT4 monotherapy. Nevertheless, these differences disappeared when introducing other elements in the analysis (prior healthcare experiences and expectations on treatment) [57]. This study suggested that improving the patient experience and clarifying expectations at diagnosis could improve satisfaction and quality of life [57].…”
Section: Discussionmentioning
confidence: 84%
“…Nevertheless, these differences disappeared when introducing other elements in the analysis (prior healthcare experiences and expectations on treatment) [57]. This study suggested that improving the patient experience and clarifying expectations at diagnosis could improve satisfaction and quality of life [57]. Several studies have researched the effect of the LT3/LT4 combination instead of LT4 monotherapy; however, although some patients prefer the LT3/LT4 combination, the evidence does not conclusively show a clear benefit of this combined therapy [5,18].…”
Section: Discussionmentioning
confidence: 87%
“…The ATA guidance about the lower limit of TSH is complex and the message not easy to communicate. A widespread belief among hypothyroid patients is that a low TSH of no consequence, hence selfadjustment of thyroid hormone dose based on symptoms (which often leads to over-replacement) is perceived as being safe (1,2).…”
Section: Guidelinesmentioning
confidence: 99%
“…Many hypothyroid patients use the internet as a major source of information about their diagnosis (1,2). They soon become aware that there are heated controversies and an apparent divide between some patient groups and endocrinologists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation